New treatment options for generalized myasthenia gravis - Vaitkus, Antanas; Čiauškaitė, J.; Malakauskaitė, M.; Baublytė, M. (Neurologijos seminarai, 2024)
Myasthenia gravis is an autoimmune disease in which autoantibodies against the postsynaptic membrane proteins of the neuromuscular junction disrupt impulse transmission thus causing pathological muscle weakness and fatigue that worsens throughout the day. Although the disease is not yet curable, most patients can achieve complete symptom control and improved quality of life with appropriate treatment. Four treatment strategies are used in clinical practice: symptomatic, immunosuppressive, immunomodulatory, and surgical treatment, which can help control the disease but are not equally effective for all patients. Symptomatic treatment with acetylcholinesterase (AChE) inhibitors is often not effective enough, so additional treatment with immunosuppressants is indicated. These are effective, but can cause systemic side effects if taken for long periods. Even polytherapy is often not sufficient enough to treat patients with myasthenia gravis. The challenges of treating this disease are encouraging to seek alternatives. Increasing attention is being paid to antibodies against acetylcholine receptors (AChRs) and other structures of the neuromuscular junction that are important in pathogenesis of myasthenia gravis. Drugs are being developed that target specific links in the immune system to reduce the risk of systemic adverse effects. Currently, only two drugs are approved for the treatment of generalized myasthenia gravis – eculizumab and efgartigimod. Both of them are safe and effective in treating generalized myasthenia gravis with prevalent anti-AChR antibodies. Currently, 10 other drugs are clinically tested for their safety and efficacy in treating patients with myasthenia gravis. In this article, we review publications that analyze biological therapy and its novelty in the treatment of myasthenia gravis. We focus more on already approved biological drugs.